Utilizing Dimensions of Critical Literacy to Improve Active Learning in Teaching English Novels in Lesotho - Mabohlokoa Masunhloane; Rantsie Kgothule (E-Journal of Humanities, Arts and Social Sciences, 2023)
English is the language of learning and teaching in many countries, as in Lesotho. This language has a curriculum, and one of its components includes reading English novels. Although English is accorded this prestigious status in Lesotho secondary schools, minimal effort has been made to address the improvement of learners’ reading skills of English novels. With this in mind, this theoretical paper focused on teachers’ use of Critical Literacy (CL) by highlighting some literature perspectives on traditional banking education and CL, the emerging relationship between CL and Active Learning (AL), and the dimensions of CL as enhancers. The methodology used in this article is derived from the experiences of the authors and three English teachers in Lesotho schools related to the dimensions of CL in the teaching of English novels (EN). The study concluded that CL should be re-visited and recognized to enable teachers to act as the driving force in teaching EN.